دور الأنشطة الترويحية الرياضية في الوقاية من بعض الأمراض المهنية لدى أساتذة التربية البدنية والرياضية - محمد العربي; محمد الأمين بوزياني (Journal of Sport Science Technology and Physical Activities, 2025)
The study aimed to identify the prevalent occupational diseases among physical and sports education professors and make comparisons between them according professional experience ; and practicing recreational sports activities.To that effect, we used the descriptive approach on a random sample amounting to (60) professor from wilaya of Bechar, we used a questionnaire designed as a data collection tool. And after having statistically treated It turns out that back pain is the most common, and differences exist, according to professional experience for experienced professor (+15 years) .and according to practice recreational sports activities for the benefit for the non-practising professors Finally, the researchers recommended spreading the culture of recreational sports activities Among professors by activation of sports and work clubs and sports competitions